Non-isothermal pyrolysis of de-oiled microalgal biomass: Kinetics and evolved gas analysis. (December 2016) - Maurya, Rahulkumar; Ghosh, Tonmoy; Saravaia, Hitesh; Paliwal, Chetan; Ghosh, Arup; Mishra, Sandhya
Graphical abstract: Highlights: Non-isothermal pyrolysis of de-oiled microalgal biomass were evaluated by TGA-MS. Iso-conversional and model–fitting kinetics were applied for thermal decomposition. Evolved gas analysis were evaluated during pyrolysis. Three-stage thermal decomposition & three-zone volatilization of organic matters. Pyrolysis involved multi-step reactions & 3D growth rate with random nucleation. Abstract: Non-isothermal (β = 5, 10, 20, 35 °C/min) pyrolysis of de-oiled microalgal biomass (DMB) of Chlorella variabilis was investigated by TGA-MS (30–900 °C, Argon atmosphere) to understand thermal decomposition and evolved gas analysis (EGA). The results showed that three-stage thermal decomposition and three volatilization zone (100–400 °C, 400–550 °C and 600–750 °C) of organic matters during pyrolysis. The highest rate of weight-loss is 8.91%/min at 302 °C for 35 °C/min heating-rate. Kinetics of pyrolysis were investigated by iso-conversional (KAS, FWO) and model-fitting (Coats-Redfern) method. For Zone-1 and 3, similar activation energy (Ea ) is found in between KAS (α = 0.4), FWO (α = 0.4) and Avrami–Erofe'ev (n=4) model. Using the best-fitted kinetic model Avrami–Erofe'ev (n=4), Ea values (R 2  = >0.96) are 171.12 (Zone-1), 404.65 (Zone-2) and 691.42 kJ/mol (Zone-3). EGA indicate the abundance of most gases observed consequently between 200–300 °C and 400–500 °C. The pyrolysis of DMB involved multi-step reaction mechanisms for solid-state reactions having different Ea values.